2013
DOI: 10.1109/jmems.2013.2241394
|View full text |Cite
|
Sign up to set email alerts
|

Forming Microgears by Micro-FAST Technology

Abstract: The use of microcomponents as well as intensive competition on manufacturing cost led to the requirement for cost-effective production of those components without much compromise on their final quality. To address this issue, a novel microforming technology, named as micro-field-activated sintering technology (Micro-FAST), was introduced for the fabrication of microcomponents, in which loose powders were pressed and sintered to form microgears via electroheating loop sintering and microforming. The whole proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…This period is defined as the main densification realized process where the axial reduction increases rapidly (from -2.9553 mm to -3.3455 mm) with the temperature rising, which is shown in Fig.3. It is worth mentioning that there was a very obvious axial shrinkage of sample that occurred, which is a result of deformation and interface melting of particles and has been noted by authors [5,6,11]. (iv).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…This period is defined as the main densification realized process where the axial reduction increases rapidly (from -2.9553 mm to -3.3455 mm) with the temperature rising, which is shown in Fig.3. It is worth mentioning that there was a very obvious axial shrinkage of sample that occurred, which is a result of deformation and interface melting of particles and has been noted by authors [5,6,11]. (iv).…”
Section: Resultsmentioning
confidence: 65%
“…A novel micro-forming technology, named Micro-FAST (combining micro-forming and FAST), was proposed recently by the present authors for the forming of micro-components. Gears made of 316L stainless and Cu powder at the micro-scale have been fabricated successfully [5,6]. As the process illustrated in Fig.1, Micro-FAST is a method which can be used for the forming of micro-components with a variety of material systems, for instance, metals, ceramics and composites.…”
Section: Introductionmentioning
confidence: 99%
“…This paper demonstrated that Micro-FAST is a promising process for the rapid forming of microcomponents with a wide range of materials, especially with difficult-to-cut and difficult-to-form 10001-p. 6 ICNFT 2015 materials. The sintering time can be shortened with the optimised sintering parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The main differences between this process with SPS and others are: AC current applied for high heating efficiency; larger heating rate-, holding time-and pressure-dependent densification; and moreover, simplified process setup and control. Encouraging findings have been made using Micro-FAST with metallic materials [5,6]; however, the feasibility of forming ceramic materials still needs to be investigated further.…”
Section: Introductionmentioning
confidence: 99%
“…2. A relative density of 98.7% was achieved [3]. Micro-parts can be prepared in a short time (about 10 min) with a high relative density (over 90%) through Micro-FAST, indicating that Micro-FAST is more effective way in comparison with the traditional sintering technology.…”
Section: Introductionmentioning
confidence: 90%